Metamorphoses of electronic structure of FeSe-based superconductors (Review Article) - Yu.V., Pustovit; Kordyuk, A.A. (Физика низких температур, 2016)
The electronic structure of FeSe, the simplest iron-based superconductor (Fe-SC), conceals a potential of dramatic increase of Tc that realizes under pressure or in a single layer film. This is also the system where nematicity, the phenomenon of a keen current interest, is most easy to study since it is not accompanied by the antiferomagnetic transition like in all other Fe-SC’s. Here we overview recent experimental data on electronic structure of FeSe-based superconductors: isovalently doped crystals, intercalates, and single layer films, trying to clarify its topology and possible relation of this topology to superconductivity. We argue that the marked differences between the experimental and calculated band structures for all FeSe compounds can be described by a hoping selective renormalization model for a spin/orbital correlated state that may naturally explain both the evolution of the band structure with temperature and nematicity.